Energy conversion device substrate and manufacturing method thereof

By adding sodium potassium glass powder to the KNN-BNT ceramic powder, the problem of internal defects in the sintering process of the energy conversion device substrate is solved, and the effect of improving ceramic voltage constant.

CN119350022APending Publication Date: 2025-01-24SHENZHEN SUNLORD ELECTRONICS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411462418.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing energy conversion device substrates are prone to internal defects during the sintering process, resulting in a low piezoelectric constant.

Method used

Adding soda-potassium glass powder to KNN-BNT ceramic powder can supplement volatilized Na+, K+ and Bi2+, ​​thereby reducing the occurrence of internal defects.

Benefits of technology

By adding sodium and potassium glass powder, it can maintain or improve ceramic voltage constant (D33), and there is no significant negative effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350022A_ABST
    Figure CN119350022A_ABST
Patent Text Reader

Abstract

The invention relates to an energy conversion device substrate, the energy conversion device substrate contains the elements of K, Na, Si, Nb, Sb, Bi and Zr, and the molar ratio of the elements of K to Na to Si to Nb to Sb to Bi to Zr is (22.04 to 25.55) to (24.96 to 27.48) to (0.005 to 1.5) to (45.12 to 47.10) to (0.44 to 1.37) to (0.45 to 1.42) to (1.40 to 2.36). According to the method, the energy conversion device substrate is prepared by adding the sodium-potassium glass into the ceramic, the effect of supplementing volatile Na < + > and K < + > is achieved, and experiments prove that the piezoelectric constant (D33) of the ceramic can be kept or improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an energy conversion device substrate and a manufacturing method thereof, in particular to a device substrate for realizing conversion between mechanical and electrical energy. Background Art

[0002] Energy conversion devices that achieve the conversion between mechanical and electrical energy, such as piezoelectric ceramics, have a wide range of uses. They are widely used as functional materials in the fields of communications, energy, aerospace, etc. Seeking to replace harmful lead zirconate titanate (PZT)-based energy conversion device materials, the demand for environmentally clean and harmless energy conversion device materials is increasing. KNN-BNT ceramics, such as 0.96K 0.48 Na 0.52 Nb 0.98 Sb 0.02 O3-0.04Bi 0.5 Na 0.5 ZrO3 is a lead-free energy conversion device with excellent performance, but its disadvantage is that internal defects are generated after sintering, resulting in a low piezoelectric constant.

[0003] It should be noted that the information disclosed in the above-mentioned background technology section is only used for understanding the background of the present application, and therefore may include information that does not constitute prior art known to a person of ordinary skill in the art. That is, the background section of the present invention may contain background information about the problem or environment of the present invention, but not necessarily a description of prior art. Therefore, the content contained in the background technology section is not an admission of prior art by the applicant. Summary of the invention

[0004] The purpose of the present invention is to overcome the disadvantage of low piezoelectric constant caused by defects in the structure of energy conversion devices in the prior art, and to provide an energy conversion device substrate and a manufacturing method thereof to maintain or improve the piezoelectric constant of ceramics.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A substrate for an energy conversion device, which contains K, Na, Si, Nb, Sb, Bi, and Zr elements, and the molar ratio of each element is K:Na:Si:Nb:Sb:Bi:Zr=(22.04-25.55):(24.96-27.48):(0.005-1.5):(45.12-47.10):(0.44-1.37):(0.45-1.42):(1.40-2.36).

[0007] In some embodiments, the energy conversion device substrate is made of KNN-BNT ceramic powder and sodium potassium glass powder, wherein:

[0008] The KNN-BNT ceramic powder is made of ceramic raw materials of the following components:

[0009] K2O: 21.50-23.55 mol%;

[0010] Na2O: 24.40-26.43 mol%;

[0011] Nb2O5: 46.04-47.54mol%;

[0012] Sb2O3: 0.46-1.40mol%;

[0013] Bi2O3: 0.50-1.48mol%;

[0014] ZrO2: 2.92-4.92mol%;

[0015] The sodium-potassium glass powder is made of the following components:

[0016] Na2O: 0.1-75 mol%;

[0017] K2O: 0.1-75 mol%;

[0018] SiO2: 0.1-95 mol%;

[0019] Preferably, the energy conversion device substrate is made of 95.0-99.5 wt. % of KNN-BNT ceramic powder and 0.5-5 wt. % of sodium potassium glass powder.

[0020] The present invention also proposes a method for manufacturing an energy conversion device substrate, comprising the following steps: S1, preparing KNN-BNT ceramic powder; S2, preparing sodium-potassium glass powder; S3, mixing the KNN-BNT ceramic powder and the sodium-potassium glass powder evenly, granulating and sieving the mixed raw materials, pressing the sieved raw materials into shape, and sintering to prepare the energy conversion device substrate.

[0021] In some embodiments, the following features are also included:

[0022] In the step S1, when preparing KNN-BNT ceramic powder, the proportions of the components of the ceramic raw materials are as follows: K2O: 21.50-23.55 mol%; Na2O: 24.40-26.43 mol%; Nb2O5: 46.04-47.54 mol%; Sb2O3: 0.46-1.40 mol%; Bi2O3: 0.50-1.48 mol%; ZrO2: 2.92-4.92 mol%.

[0023] The step S1 includes a pre-burning step, the pre-burning temperature is 750-900° C., and the pre-burning time is 2-10 hours.

[0024] In the step S2, when the sodium potassium glass powder is prepared, the proportions of the components are as follows: Na2O: 0.1-75mol%; K2O: 0.1-75mol%; SiO2: 0.1-95mol%.

[0025] The step S2 includes a smelting step, the smelting temperature is 1300-1500° C., and the smelting time is 0.5-4 hours.

[0026] In the step S3, the ratios of KNN-BNT ceramic powder and sodium potassium glass powder are 95.0-99.5 wt. % and 0.5-5 wt. %, respectively.

[0027] In the step S3, the sintering temperature is 900-1100° C. and the temperature is kept for 1-3 hours.

[0028] In the step S3, the sieved raw material is pressed and formed at 100-200 MPa.

[0029] The present invention has the following beneficial effects: The inventors have found that due to the high sintering temperature of KNN-BNT ceramics (for example, about 1150°C), at this high temperature, the sintering process Na + , K + and Bi 2+ Therefore, when preparing the energy conversion device substrate, sodium potassium glass is added to the KNN-BNT ceramic powder to prevent the volatilization of Na + , K + Experiments have shown that it can maintain or improve the ceramic piezoelectric constant (D33) without producing any obvious negative effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The figure is a schematic diagram of the process flow of an embodiment of the present invention.

[0031] Figure 2 This is a SEM image of the energy conversion device substrate prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention.

[0033] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the embodiments of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0034] like Figure 1 The following is a process for preparing, sintering and testing the substrate material of the energy conversion device according to the embodiment of the present application. It includes:

[0035] Step 1

[0036] Preparation process of KNN-BNT ceramic powder: weigh KNN-BNT ceramic raw materials K2O: 21.50-23.55mol%; Na2O: 24.40-26.43mol%; Nb2O5: 46.04-47.54mol%; Sb2O3: 0.46-1.40mol%; Bi2O3: 0.50-1.48mol%; ZrO2: 2.92-4.92mol% in proportion, a total of 100-500g is placed in a polytetrafluoroethylene plastic bottle, 50-250g of ethanol is poured in, and the mixture is rolled at a speed of 500-1200rpm for 6-24h. The evenly mixed raw materials are dried at a temperature of 60-100℃ for 12-24h to remove the ethanol. The dried raw powder is heated to 750-900°C at 1-10°C / min and pre-fired for 2-10h. 50-100g of the pre-fired powder is placed in an agate jar. 50-100g of ethanol and 150-300g of 3-10mm zirconium balls are added and ball-milled at 500-1000rpm for 6-24h. The powder is dried at 60-100°C for 12-24h to remove the ethanol, and KNN-BNT ceramic powder can be prepared.

[0037] Step 2

[0038] Preparation process of sodium potassium glass powder: weigh 100-500g of raw materials of Na2O (0.1-75mol%), K2O (0.1-75mol%), and SiO2 (0.1-95mol%) and put them in a polytetrafluoroethylene plastic bottle, roll ball mill at a speed of 500-1200rpm for 6-12h, and then smelt the mixed raw materials at a temperature of 1300-1500℃ for 0.5-4h, and then pour deionized water to quench to prepare glass slag. Take 50-100g of glass slag and put it in an agate pot, add 50-100g of ethanol and 150-300g of 3-10mm zirconium balls, and then ball mill at a speed of 800-1000rpm for 4-24h, and dry it at a temperature of 60-100℃ for 12-24h to remove ethanol, and then prepare sodium potassium glass powder.

[0039] Step 3

[0040] Preparation process of energy conversion device substrate: weigh 100-200g of KNN-BNT ceramic powder (95.0-99.5wt.%) obtained in step 1 and sodium potassium glass powder (0.5-5wt.%) obtained in step 2 and put them in a polytetrafluoroethylene plastic bottle, pour in 50-100g of ethanol and roll ball mill at a speed of 500-1000rpm for 6-24h, and dry the evenly mixed raw materials at a temperature of 60-100℃ for 12-24h to remove ethanol. Take 50-100g of the mixed raw materials, add 2-10g of 5-10wt% PVB (polyvinyl butyral) alcohol solution to granulate and pass through an 80-100 mesh sieve. After the sieved raw materials, weigh 0.5-1g and press into shape at 100-200MPa. Then, put it in a sintering furnace and heat it to 450-600℃ at 1-2℃ / min to debind for 2-4h, continue to heat it to 900-1100℃ at 3-10℃ / min, and keep it warm for 1-3h to prepare the energy conversion device substrate.

[0041] Example

[0042] Embodiment 1

[0043] Weigh 200g of KNN-BNT ceramic raw materials K2O (22.59mol%), Na2O (25.45mol%), Nb2O5 (46.12mol%), Sb2O3 (0.94mol%), Bi2O3 (0.98mol%), and ZrO2 (3.92mol%) in proportion and put them in a polytetrafluoroethylene plastic bottle. Pour 100g of ethanol and roll ball mill at 800rpm for 12h. The mixed raw materials are dried at 80℃ for 18h to remove ethanol. The dried raw material powder is heated to 850℃ at 5℃ / min for 2h. 100g of the pre-burned powder is put in an agate pot, 50g of ethanol and 300g of 5mm zirconium balls are added, and the mixture is ball milled at 800rpm for 12h. It is dried at 70℃ for 18h to remove ethanol to prepare KNN-BNT ceramic powder.

[0044] Weigh 200g of raw materials of Na2O (0.5mol%), K2O (0.5mol%), and SiO2 (90mol%) and put them in a polytetrafluoroethylene plastic bottle, roll and ball mill them at 800rpm for 12h, melt the mixed raw materials at 1400℃ for 1h, pour them into deionized water for quenching to prepare glass slag. Take 100g of glass slag and put it in an agate pot, add 100g of ethanol and 300g of 5mm zirconium balls, ball mill them at 800rpm for 12h, dry them at 80℃ for 18h to remove ethanol, and prepare sodium potassium glass powder.

[0045] Weigh 100g of KNN-BNT ceramic powder (96.0wt.%) and sodium potassium glass powder (4wt.%) in a polytetrafluoroethylene plastic bottle, pour 50g of ethanol and roll mill at 800rpm for 18h, dry the mixed raw materials at 70℃ for 18h to remove ethanol. Take 50g of the mixed raw materials, add 6g of 5wt% PVB alcohol solution to granulate and pass through an 80-mesh sieve, weigh 0.5g of the sieved raw materials, press mold at 120MPa, put in a sintering furnace, heat to 550℃ at 2℃ / min to remove binder for 4h, continue to heat to 900℃ at 5℃ / min and keep warm for 2h to prepare energy conversion device substrate (ceramic substrate).

[0046] The ceramic piezoelectric constant D33 of the ceramic substrate tested was 320 pC / N.

[0047] Figure 2 3 is a SEM image of the KNN-BNT energy conversion device substrate prepared in Example 1 of the present invention. The distribution of sodium-potassium glass in the KNN-BNT ceramic substrate can be seen from the SEM image (the dark gray part in the figure represents sodium-potassium glass).

[0048] Embodiment 2

[0049] The KNN-BNT ceramic powder was prepared by the same method as in Example 1.

[0050] The sodium-potassium glass powder was prepared in the same manner as in Example 1.

[0051] Weigh 100g of KNN-BNT ceramic powder (99.0wt.%) and sodium potassium glass powder (1wt.%) in a polytetrafluoroethylene plastic bottle, pour 50g of ethanol and roll mill at 800rpm for 18h, dry the mixed raw materials at 70℃ for 18h to remove ethanol. Take 50g of the mixed raw materials, add 6g of 5wt% PVB alcohol solution to granulate and pass through an 80-mesh sieve, weigh 0.5g of the sieved raw materials, press mold at 120MPa, put in a sintering furnace, heat to 550℃ at 2℃ / min to remove binder for 4h, continue to heat to 975℃ at 5℃ / min and keep warm for 2h to prepare energy conversion device substrate.

[0052] The ceramic substrate was taken to test the ceramic piezoelectric constant D33, which was 350pC / N.

[0053] Embodiment 3

[0054] The KNN-BNT ceramic powder was prepared by the same method as in Example 1.

[0055] 200g of raw materials of Na2O (70mol%), K2O (29.5mol%) and SiO2 (0.5mol%) were weighed and placed in a polytetrafluoroethylene plastic bottle, and rolled at 800rpm for 12h. The mixed raw materials were melted at 1400℃ for 1h and then poured into deionized water for quenching to prepare glass slag. 100g of glass slag was placed in an agate pot, 100g of ethanol and 300g of 5mm zirconium balls were added, and the mixture was ball-milled at 800rpm for 12h, and dried at 80℃ for 18h to remove ethanol, and sodium potassium glass powder was prepared.

[0056] Weigh 100g of KNN-BNT ceramic powder (96.0wt.%) and sodium potassium glass powder (4wt.%) in a polytetrafluoroethylene plastic bottle, pour 50g of ethanol and roll ball mill at 800rpm for 18h, dry the mixed raw materials at 70℃ for 18h to remove ethanol. Take 50g of the mixed raw materials, add 6g of 5wt% PVB alcohol solution to granulate and pass through an 80-mesh sieve, weigh 0.5g of the sieved raw materials, press mold at 120MPa, put them in a sintering furnace, heat up to 550℃ at 2℃ / min to remove binder for 4h, continue to heat up to 910℃ at 5℃ / min and keep warm for 2h to prepare energy conversion device substrate.

[0057] The ceramic substrate was taken to test the ceramic piezoelectric constant D33, which was 390pC / N.

[0058] Embodiment 4

[0059] The KNN-BNT ceramic powder was prepared by the same method as in Example 1.

[0060] 200g of raw materials of Na2O (29.5mol%), K2O (70mol%) and SiO2 (0.5mol%) were weighed and placed in a polytetrafluoroethylene plastic bottle, and rolled at 800rpm for 12h. The mixed raw materials were melted at 1400℃ for 1h and then poured into deionized water for quenching to prepare glass slag. 100g of glass slag was placed in an agate pot, 100g of ethanol and 300g of 5mm zirconium balls were added, and the mixture was ball-milled at 800rpm for 12h, and dried at 800℃ for 18h to remove ethanol, and sodium potassium glass powder was prepared.

[0061] Weigh 100g of KNN-BNT ceramic powder (98.0wt.%) and sodium potassium glass powder (2wt.%) in a polytetrafluoroethylene plastic bottle, pour 50g of ethanol and roll mill at 800rpm for 18h, dry the mixed raw materials at 70℃ for 18h to remove ethanol. Take 50g of the mixed raw materials, add 6g of 5wt% PVB alcohol solution to granulate and pass through an 80-mesh sieve, weigh 0.5g of the sieved raw materials, press mold at 120MPa, put in a sintering furnace, heat to 550℃ at 2℃ / min to remove binder for 4h, continue to heat to 950℃ at 5℃ / min and keep warm for 2h to prepare energy conversion device substrate.

[0062] The ceramic substrate was taken to test the ceramic piezoelectric constant D33, which was 430pC / N.

[0063] Embodiment 5

[0064] The KNN-BNT ceramic powder was prepared by the same method as in Example 1.

[0065] Sodium potassium glass powder was prepared by the same method as in Example 3.

[0066] Weigh 100g of KNN-BNT ceramic powder (99.0wt.%) and sodium potassium glass powder (1wt.%) in a polytetrafluoroethylene plastic bottle, pour 50g of ethanol and roll ball mill at 800rpm for 18h, dry the mixed raw materials at 70℃ for 18h to remove ethanol. Take 50g of the mixed raw materials, add 6g of 5wt% PVB alcohol solution to granulate and pass through an 80-mesh sieve, weigh 0.5g of the sieved raw materials, press mold at 120MPa, put them in a sintering furnace, heat up to 550℃ at 2℃ / min to remove binder for 4h, continue to heat up to 980℃ at 5℃ / min and keep warm for 2h to prepare energy conversion device substrate.

[0067] The ceramic substrate was taken to test the ceramic piezoelectric constant D33, which was 480pC / N.

[0068] Comparative Example

[0069] Comparative Example 1

[0070] The KNN-BNT ceramic powder was prepared by the same method as in Example 1.

[0071] Take 50g of ceramic powder, add 6g of 5wt% PVB alcohol solution to granulate and pass through an 80-mesh sieve. After sifting, weigh 0.5g of the raw material and press it into shape at 120MPa. Then put it in a sintering furnace and heat it to 550℃ at 2℃ / min to debind for 4h. Continue to heat it to 1120℃ at 5℃ / min and keep it warm for 2h to prepare the KNN-BNT energy conversion device substrate.

[0072] The ceramic substrate was taken to test the ceramic piezoelectric constant D33, which was 310pC / N.

[0073] Comparative Example 2

[0074] The KNN-BNT ceramic powder was prepared by the same method as in Example 1.

[0075] Take 50g of ceramic powder, add 6g of 5wt% PVB alcohol solution, granulate and pass through an 80-mesh sieve. Weigh 0.5g of the sieved raw material and press it into shape at 120MPa. Then put it in a sintering furnace and heat it to 550℃ at 2℃ / min to debind for 4h. Continue to heat it to 1130℃ at 5℃ / min and keep it warm for 2h to prepare the KNN-BNT energy conversion device substrate.

[0076] The ceramic substrate was taken to test the ceramic piezoelectric constant D33, which was 300pC / N.

[0077] In summary, the above embodiments have the following technical effects:

[0078] On the one hand, it can reduce costs; on the other hand, it can reduce defects inside the ceramics, thereby improving the piezoelectric properties of the ceramics.

[0079] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, it can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description of the reference terms "an embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In the absence of mutual contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the scope of protection of the patent application.

Claims

1. An energy conversion device substrate, characterized in that: The energy conversion device substrate contains K, Na, Si, Nb, Sb, Bi, and Zr elements, and the molar ratio of each element is K:Na:Si:Nb:Sb:Bi:Zr=(22.04-25.55):(24.96-27.48):(0.005-1.5):(45.12-47.10):(0.44-1.37):(0.45-1.42):(1.40-2.36).

2. The energy conversion device substrate according to claim 1, characterized in that: The energy conversion device substrate is made of KNN-BNT ceramic powder and sodium potassium glass powder, wherein: The KNN-BNT ceramic powder is made of ceramic raw materials of the following components: K2O: 21.50-23.55 mol%; Na2O: 24.40-26.43 mol%; Nb2O5: 46.04-47.54mol%; Sb2O3: 0.46-1.40mol%; Bi2O3: 0.50-1.48mol%; ZrO2: 2.92-4.92mol%; The sodium-potassium glass powder is made of the following components: Na2O: 0.1-75 mol%; K2O: 0.1-75 mol%; SiO2: 0.1-95 mol%; Preferably, the energy conversion device substrate is made of 95.0-99.5 wt. % of KNN-BNT ceramic powder and 0.5-5 wt. % of sodium potassium glass powder.

3. A method for manufacturing an energy conversion device substrate, characterized in that: The steps include: S1. preparing KNN-BNT ceramic powder; S2, preparing sodium potassium glass powder; S3. Evenly mix the KNN-BNT ceramic powder and the sodium potassium glass powder, granulate the mixed raw materials and sieve them, press the sieved raw materials into shapes, and sinter them to prepare an energy conversion device substrate.

4. The method for manufacturing an energy conversion device substrate according to claim 3, characterized in that: In step S1, when preparing KNN-BNT ceramic powder, the proportions of the components of the ceramic raw materials are as follows: K2O: 21.50-23.55 mol%; Na2O: 24.40-26.43 mol%; Nb2O5: 46.04-47.54mol%; Sb2O3: 0.46-1.40mol%; Bi2O3: 0.50-1.48mol%; ZrO2: 2.92-4.92mol%.

5. The method for manufacturing an energy conversion device substrate according to claim 3, wherein: The step S1 includes a pre-burning step, the pre-burning temperature is 750-900° C., and the pre-burning time is 2-10 hours.

6. The method for manufacturing an energy conversion device substrate according to claim 3, wherein: In step S2, when preparing sodium potassium glass powder, the proportions of the components are as follows: Na2O: 0.1-75 mol%; K2O: 0.1-75 mol%; SiO2: 0.1-95 mol%.

7. The method for manufacturing an energy conversion device substrate according to claim 3, characterized in that: The step S2 includes a smelting step, the smelting temperature is 1300-1500° C., and the smelting time is 0.5-4 hours.

8. The method for manufacturing an energy conversion device substrate according to claim 3, wherein: In the step S3, the ratios of KNN-BNT ceramic powder and sodium potassium glass powder are 95.0-99.5 wt. % and 0.5-5 wt. %, respectively.

9. The method for manufacturing an energy conversion device substrate according to claim 3, wherein: In the step S3, the sintering temperature is 900-1100° C. and the temperature is kept for 1-3 hours.

10. The method for manufacturing an energy conversion device substrate according to claim 3, characterized in that In step S3, the sieved raw materials are pressed and formed at 100-200 MPa.

Citation Information

Patent Citations

  • Glass-dust-doped high-energy-density lead-free ferroelectric thick film and preparation method

    CN103021653A

  • Niobium sodium potassium antimonate-potassium sodium bismuth zirconate leadless piezoelectric ceramic with high piezoelectric constant and preparation method thereof

    CN103482977A

  • Bioglass ceramic doped with potassium-sodium niobate and preparation method of bioglass ceramic

    CN108794003A

  • Potassium-sodium niobate-based ceramic with high piezoelectric property and preparation method of potassium-sodium niobate-based ceramic

    CN113896532A

  • Ceramic sheet, method for producing the same, and method for producing crystallographically-oriented ceramic

    JP2009046376A